A PRODUÇÃO E REPRESENTAÇÃO DE ESTRUTURAS TERRITORIAIS: O CASO DO ASSENTAMENTO 08 DE ABRIL - JARDIM ALEGRE/PR - Denez, Cleiton Costa (2011)
This paper aims to present the territory and territoriality production and the April 8th Settlement by examining the relationship of the subjects involved in this venue. For this purpose, it analyzed education, production and socio-political organization in the Settlement. Raffestin’s theory (2009) was used in order to understand the construction of territorialities and how they are produced and manifested in the Settlement. Such theory addresses the elements and subjects involved in the territorial production. This author works with the “production of territorial structures and their representation”. Therefore, some of this theory was applied in praxis to the construction of the April 8th Settlement territorialities. The settlement takes place through the articulation of its political organization in the different relational processes that occur within it. This settlement produces the territorialities, which are the fruits of the process of confrontation and correlation of interests of Market x State x Landless Movement (MST) = Settlement. These processes produce the territorialities within the settlement. Concurrently, they characterize the "April 8th" and its microterritoriality with regard to other territorial structures such as the MST, the Market and the State are depicted as macroterritorialities.